Functional Electrical Stimulation: A Possible Strategy to Improve Muscle Function in Central Core Disease? - Iodice, Pierpaolo; Boncompagni, Simona; Pietrangelo, Laura; Galli, Lucia; Pierantozzi, Enrico; Rossi, Daniela; Fusella, Aurora; Caulo, Massimo; Kern, Helmut; Sorrentino, Vincenzo; Protasi, Feliciano (Frontiers in Neurology, 2019)
Central Core Disease (CCD) is a congenital myopathy characterized by presence of amorphous central areas (or cores) lacking glycolytic/oxidative enzymes and mitochondria in skeletal muscle fibers. Most CCD families are linked to mutations in ryanodine receptor type-1 (RYR1), the gene encoding for the sarcoplasmic reticulum (SR) Ca2+ release channel of skeletal muscle. As no treatments are available for CCD, currently management of patients is essentially based on a physiotherapic approaches. Functional electrical stimulation (FES) is a technique used to deliver low energy electrical impulses to artificially stimulate selected skeletal muscle groups. Here we tested the efficacy of FES in counteracting muscle loss and improve function in the lower extremities of a 55-year-old female patient which was diagnosed with CCD at the age of 44. Genetic screening of the RyR1 gene identified a missense mutation (c.7354C>T) in exon 46 resulting in an amino acid substitution (p.R2452W) and a duplication (c.12853_12864dup12) in exon 91. The patient was treated with FES for 26 months and subjected before, during, and after training to a series of functional and structural assessments: measurement of maximum isometric force of leg extensor muscles, magnetic resonance imaging, a complete set of functional tests to assess mobility in activities of daily living, and analysis of muscle biopsies by histology electron microscopy. All results point to an improvement of muscle structure and function induced by FES suggesting that this approach could be considered as an additional supportive measure to maintain/improve muscle function and reduce muscle loss in CCD patients.